2006
DOI: 10.1260/026361706781388941
|View full text |Cite
|
Sign up to set email alerts
|

Direct Determination of the Intermolecular Structure of the Adsorbed Phase Using in situ X-Ray Diffraction and Reverse Monte Carlo Methods

Abstract: A new direct method for determining the intermolecular structure of molecular assemblies in micropores using reverse Monte Carlo (RMC) simulation is proposed. The method gives the molecular configuration in an adsorption phase using experimental X-ray diffraction profiles and an assumed pore structure. This method has been applied to a carbon/water adsorption system to confirm previous results for the cluster formation of water in a hydrophobic space. The RMC method is a useful tool for estimating the pseudo-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
14
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 17 publications
4
14
0
Order By: Relevance
“…As noted above, clustering of water in hydrophobic nanopores at moderate loading has been experimentally observed in [19,21] by in situ SAXS and in situ XRD. In simulations, this effect can be qualitatively observed through direct visualisation of the water molecules within the pore, and can be quantitatively characterised by calculation of the radial distribution function g(r) that for two particles of the same species is,…”
Section: Water Structure and Transport Propertiesmentioning
confidence: 56%
See 2 more Smart Citations
“…As noted above, clustering of water in hydrophobic nanopores at moderate loading has been experimentally observed in [19,21] by in situ SAXS and in situ XRD. In simulations, this effect can be qualitatively observed through direct visualisation of the water molecules within the pore, and can be quantitatively characterised by calculation of the radial distribution function g(r) that for two particles of the same species is,…”
Section: Water Structure and Transport Propertiesmentioning
confidence: 56%
“…Both experimental and simulation results have identified that water in hydrophobic and/or nanoporous structures forms clusters at some loadings [19][20][21]. Small-angle x-ray scattering (SAXS) experiments and grand canonical Monte Carlo (GCMC) studies have shown that water molecules begin to form clusters that are 6 Å in diameter at 0.6 relative pressure (P/P 0 ) within a 11 Å width slit-pore and the cluster size becomes bigger with increasing the pressure (higher water loading) due to combination of clusters [19].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, we reported preliminary results of the RMC simulation for water adsorbed in micropores of an activated carbon fiber [28].…”
Section: Introductionmentioning
confidence: 99%
“…13,14 In this case, geometrical parameters of the adsorbent and adsorbate were used to deduce the molecular arrangement, which reproduces the experimental scattering profiles. 15,16 We used this technique for separating the intra-and intermolecular OO, OD, and DD contributions, and the contributions of carbon and D 2 O. The detailed procedure and three-dimensional structure analysis using a snapshot of the RMC simulation will be described in a future article.…”
Section: 8mentioning
confidence: 99%